Improved crop management practices for sustainable pulse production: An Indian perspective - POONIYA, VIJAY; CHOUDHARY, ANIL K; DASS, ANCHAL; BANA, R S; RANA, K S; RANA, D S; TYAGI, V K; PUNIYA, M M (The Indian Journal of Agricultural Sciences, 2015)
Pulses are an integral part of Indian agricultural economy next to cereals and oilseeds in terms of acreage, production and economic value. Pulses are rich source of protein and energy, but in India, these are largely cultivated under energy starved conditions resulting in poor pulse productivity. This is mainly because of unavailability of quality seed at desired time, cultivation on marginal and sub-marginal lands, imbalanced use of fertilizers and nonadoption of crop improved management practices. India is the largest producer and consumer of pulses in the world, accounting for about 25% of global production, 27% of consumption and 34% of food use. To reduce the demandsupply gap, government of India launched various programmes in pulses. Still, prime attention is required to meet the food security challenges, especially in case of pulse sector. In order to enhance and sustain the pulse productivity at high levels, the development and promotion of low–cost pulse production technology need greater attention so that technology is widely adopted by the practizing farmers. The most potential technologies in pulse production include improved crop establishment and management practices, integrated soil fertility and pest management practices, etc. which enhance not only the productivity and profitability but also warrants environmental and social sustainability besides nutritional security. Various agronomic researches have shown that improved cultivation practices, such as seed replacement with improved varieties, raised bed planting method, use of biofertilizers, foliar application of fertilizers at critical stages in rainfed areas, application of secondary and micro-nutrients and adoption of appropriate modules for integrated weed and pest management, etc. have great potential in gearing-up pulses productivity. Thus, there is a great challenge for policy makers, farm scientists and farming community to enhance pulse productivity using improved farm technology to meet out the national and local pulse requirements. Thus, this article presents a critical review on capacity of various improved crop management practices to scale-up pulses productivity on one hand and highlight future research priorities on the other with the prime objective of sustaining pulse production in India.